IDEA picture dictionary. 1 : an IDEA language development resource. (Brea, CA : Ballard & Tighe, 2004)
A dictionary for early elementary grades, with each word portrayed in the accompanying illustration. Words are also given in Spanish, Vietnamese, Hmong, Filipino, Chinese, and French.
"With links to fun activities online"--Cover.
Keywords: English language -- Dictionaries, Juvenile; Spanish language -- Dictionaries, Juvenile; Picture dictionaries, Polyglot -- Juvenile literature